Our factory : textile workers' memories and experiences in Slovenia - Vodopivec, Nina (Array, 2020)
The article deals with textile workers’ memories of a socialist factory and industrial work in Slovenia, and their experiences during numerous contemporary restructurings and social transformations. It argues that textile workers were heavily marked by the disintegration of their community and loss of social recognition. The loss of the factory was experienced as personal and social loss, the loss of dignity and self-worth. Such experiences are connected to historically shaped meanings of factories, the role and position of industrial workers in the past socialist landscape, with particular memories and experiences of work. The metanarrative of socialist industrialization depicted them as protagonists of modernization and social development. They were co-creators of the industrial miracle, local infrastructure and social standard. They now felt robbed and dispossessed in a material and symbolic sense. The society showed little interest in their experience of such a loss. The absence of research and little attention paid to such questions by the society is connected to the way in which the society dealt with economic restructuring in Slovenia. The local experience is compared with other post-socialist ethnographies and industrial worker ethnographies in the transformed capitalist world.